EFFECT OF ARBUSCULAR MYCORRHIZAL INOCULATION AND THE KIND OF MANURE ON GROWTH AND YIELD OF CORN IN PEAT SOIL - FEBRIYANTI AS; Dwi Zulfita; Putu Dupa Bandem (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTThe research aims to know the best of between interaction Arbuscular MycorrhizalFungi (AMF) inoculations and the kind of manure on the growth and yield of cornon peat soil. Research conducted at the Jl. Reformasi Gg. Racana Untan, KelurahanBansir Laut, Kecamatan Pontianak Tenggara, of date of April 4, 2018 until June 24,2018. The design used was a Randomized Competely Block Design (RCBD) withtwo factors that AMF inoculation (M) and the kind of manure (P). There are 6combination of treatment, 3 replications and each replication there were 3 plantsamples. The treatments were as follows without AMF inoculation + chickenmanure (m0p1), without AMF inoculation + goat manure (m0p2), without AMFinoculation + cow manure (m0p3), inoculation AMF + chicken manure (m1p1),inoculation AMF + goat manure (m1p2), AMF inoculation + cow manure (m1p3).The variables observed in this study were plant height (cm), leaf number (sheet),root infections by mycorrhizal (%), root volume (cm3), leaf chlorophyll (spad unit),leaf area (cm2), dry weight (g), cob weight without skin (g), cob length (cm), cobdiameter (cm), and the weight a dry grain (g). The results of the research showedthere is interaction between AMF inoculations and the kind of manure on thegrowth and yield of corn on peat soil. The interaction between AMF inoculationand chicken manure showed the best growth and yield of corn on peat soil.Keywords: arbuscular mycorrhizal, animal manure, corn, peat soil.